Description Iva Test Results Women of Childbearing Age With Flour Albous at Puskesmas Medan Sunggal - Imelda, Fatwa; Santosa, Heru (Talenta Publisher, 2022)
Cervical cancer is a women's health problem in Indonesia with a high mortality rate. Delay in diagnosis at an advanced stage, weak condition, social status, low economy, limited resources, limited facilities and infrastructure, type of histopathology and degree of education participate in determining the prognosis of the patient. An effective screening that can be used is the IVA Test (Visual Acetate Inspection) which is a direct examination without using a magnification tool (the naked eye) after swabbing the cervix with 3-5% acetic acid. This community service was carried out to 44 women of childbearing age (WUS) with flour albous who did the IVA Test Puskesmas Medan Sunggal. The results of the community service that carried out the IVA Test examination on WUS The majority of WUS with flour albous were >35 years old 56.8%, married status (97.7%), Diploma/Bachelor education level was 50%, working status was (65.9%), history of parity <2 is (32%) , menstrual age > 12 years by (65.9%). IVA Test results majority of 37 people (84.1%) IVA Test was negative, and 7 people (15.9%) IVA Test was positive. It is hoped that health workers can improve education and health promotion about cervical cancer prevention by holding seminars or cervical cancer detection checks by conducting an IVA Test, and women who have done an IVA Test with a negative result can do a repeat IVA Test a year later, and on a positive IVA Test result can repeat the IVA Test 6 months later.